2020
DOI: 10.4103/jmas.jmas_163_18
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid: Evolving techniques in laparoscopic ventral hernia mesh repair

Abstract: Introduction: Laparoscopic repair is now the treatment of choice for most cases of ventral/incisional hernia. Although the technique has undergone many refinements, there is no standard technique for difficult or complicated hernias. Aim: The aim of this study was to show the different innovative methods used to treat difficult ventral hernia through hybrid techniques. Materials and Methods: A total of 75 ( n = 75) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Our study (Hybrid: Evolving techniques in laparoscopic ventral hernia mesh repair) published in journal of minimal access surgery July 2020, has similar results as compared to that of literature [18]. We have demonstrated various hybrid techniques and their post-operative outcome.…”
Section: Literaturesupporting
confidence: 64%
“…Our study (Hybrid: Evolving techniques in laparoscopic ventral hernia mesh repair) published in journal of minimal access surgery July 2020, has similar results as compared to that of literature [18]. We have demonstrated various hybrid techniques and their post-operative outcome.…”
Section: Literaturesupporting
confidence: 64%
“…After full-text reading, 12 articles were judged eligible and included for final data analysis, representing a total of 1681 patients. Two articles were the short-and long-term outcomes of one randomized controlled trial of Ahonen-Siirtola et al [10,19], and ten were retrospective cohort studies [20][21][22][23][24][25][26][27][28][29]. An overview of study characteristics including methodological quality of each included study is shown in Table 1.…”
Section: Search and Study Characteristicsmentioning
confidence: 99%
“…Amaral et al [21] used a HIHR technique in sixteen patients that commenced with a laparoscopic adhesiolysis part, continued with a laparotomy for mesh placement, and laparoscopic fixation of the mesh in the final part. This sequence is also used by Van den Dop et al [23] in 70 patients, Kudsi et al [28] in 20 patients, by Ji et al [22] in 42 patients and by Wasim et al [24], in 30 patients.…”
Section: Hihr Techniquesmentioning
confidence: 99%